Pemanfaatan Teknologi Robotika pada Perangkat Tempat Sampah di Gedung Kebaktian Jemaat GMIT Eklesia Nun Baun Delha Klasis Kota Kupang - Fransiskus Ferry Goe Ray; Yetursance Y. Manafe; I Made Parsa; Zet Y. Baitanu; Ichsan Fahmi; Gunadi Tjahjono; Louis F. Boesday; Crispinus P. Tamal; Renold H. Modok; Deprison A. Penu Djira; Benediktus Atitus; Wilhelmus H. R. Lobo (Jurnal Kelimutu Pengabdian Masyarakat, 2022)
Environmental cleanliness is a social issue that is a serious problem in people's lives, especially inurban areas. The challenge faced by the GMIT Eklesia Nun Baun Delha Congregation in terms of wastemanagement lies not only in the quantity of waste but also regarding waste management that is not yetgood. The problem is caused by the lack of availability of proper garbage disposal sites and low awareness of the congregation and the community around the location of the GMIT Eklesia Nun Baun DelhaCongregation's place of worship to dispose of waste in its place. The use of robotic technology in trash binsplaced in the GMIT Eklesia Nun Baun Delha congregation's service building is an alternative offered with theaim of reducing the amount of trash scattered around the worship building and building awareness of themembers of the GMIT Eklesia Congregation themselves to dispose of trash in the space provided. This activity was carried out using the practical method of making a trash can device. At present the GMIT EklesiaNun Baun Delha congregational worship building has a trash can that can be operated by utilizing roboticstechnology where its use is very effective.